2022
DOI: 10.3389/fneur.2022.791547
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of LASSO Regression and Tree-Based Models for Delayed Cerebral Ischemia in Elderly Patients With Subarachnoid Hemorrhage

Abstract: BackgroundsAs a most widely used machine learning method, tree-based algorithms have not been applied to predict delayed cerebral ischemia (DCI) in elderly patients with aneurysmal subarachnoid hemorrhage (aSAH). Hence, this study aims to develop the conventional regression and tree-based models and determine which model has better prediction performance for DCI development in hospitalized elderly patients after aSAH.MethodsThis was a multicenter, retrospective, observational cohort study analyzing elderly pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Recent research has shown that machine learning algorithms outperform traditional statistical modeling approaches. The RF and LASSO methods were the most widely used machine learning methods for feature selection in most literature (27)(28)(29). Especially the LASSO method might help to solve the collinearity problem.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that machine learning algorithms outperform traditional statistical modeling approaches. The RF and LASSO methods were the most widely used machine learning methods for feature selection in most literature (27)(28)(29). Especially the LASSO method might help to solve the collinearity problem.…”
Section: Discussionmentioning
confidence: 99%
“…To remove redundant features, reduce model over tting, and facilitate model interpretation, we used Spearman's correlation analysis (SPM; the threshold for the correlation coe cient was 0.7) and univariate analysis (p < 0.050). Least absolute shrinkage and selection operator (LASSO) [20,21]…”
Section: Radiomics Features Extraction and Selectionmentioning
confidence: 99%
“…Subarachnoid hemorrhage caused by ruptured intracranial aneurysms (aSAH) is a global health concern due to its significant impact on mortality and long-term disability rates [ 1 ]. Approximately 35% of patients succumb to severe cerebrovascular injury in the initial weeks [ 2 ].…”
Section: Introductionmentioning
confidence: 99%